2013
DOI: 10.4161/adip.23784
|View full text |Cite
|
Sign up to set email alerts
|

Dedifferentiated adipocyte-derived progeny cells (DFAT cells)

Abstract: Analyses of mature adipocytes have shown that they possess a reprogramming ability in vitro, which is associated with dedifferentiation. The subsequent dedifferentiated fat cells (DFAT cells) are multipotent and can differentiate into adipocytes and other cell types as well. Mature adipocytes can be easily obtained by biopsy, and the cloned progeny cells are homogeneous in vitro. Therefore, DFAT cells (a new type of stem cell) may provide an excellent source of cells for tissue regeneration, engineering and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…Different from BAT, which plays a key role in thermogenesis, WAT stores large amount of lipids and is the source of numerous adipokines which are either involved in maintenance of whole body energy balance, inflammation and numerous other aspects of fat metabolism [10, 11]. From a whole body distribution perspective BAT is generally abundant in newborns and decreases with age, whereas WAT exists widely, especially in the intra-abdominal and subcutaneous tissues [12, 13]. In humans, the excessive accumulation of WAT is a main contributing factor of obesity, which also leads to adverse health effects, such as insulin resistance, heart disease, and metabolic disorders [14].…”
Section: Adipose Tissue Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Different from BAT, which plays a key role in thermogenesis, WAT stores large amount of lipids and is the source of numerous adipokines which are either involved in maintenance of whole body energy balance, inflammation and numerous other aspects of fat metabolism [10, 11]. From a whole body distribution perspective BAT is generally abundant in newborns and decreases with age, whereas WAT exists widely, especially in the intra-abdominal and subcutaneous tissues [12, 13]. In humans, the excessive accumulation of WAT is a main contributing factor of obesity, which also leads to adverse health effects, such as insulin resistance, heart disease, and metabolic disorders [14].…”
Section: Adipose Tissue Developmentmentioning
confidence: 99%
“…Adipocytes are primarily derived from multipotent mesenchymal stem cells (MSCs) which also have the capacity to develop into osteoblasts, chondrocytes, and myoblasts through various differentiation pathways, respectively [13, 16]. Studies of mesenchymal stem cell differentiation processes have revealed an array of ‘master genes’ essential for progenitor cells into unique differentiation directions [17].…”
Section: Adipose Tissue Developmentmentioning
confidence: 99%
“…Mature adipocytes and their potential role in regenerative medicine have recently gained increased attention [13]. Previous studies have demonstrated that white adipocytes are able to reversibly change their phenotype and undergo reprogramming into other lineages, by transitioning through cells that are referred to as dedifferentiated (DFAT) cells [47].…”
Section: Introductionmentioning
confidence: 99%
“…[55][56][57][58] Related to this hypothesis, some authors have even postulated a relationship between the existence of stem cells in the ovarian surface epithelium (OSE) and the incidence of ovarian cancer of epithelial cell origin, a theory that is supported by the deregulation of cell cycle and cell signaling genes which has previously been observed. One of the possible explanations for the existence of germinal stem cells in mammalian ovaries is an ovarian cell dedifferentiation process that, under specific in vitro conditions, produces cells which are able to develop into germ-like cells in the same way as previously described for other cell types.…”
Section: Stem Cells In the Ovaries Of Female Mammals: Fallacy Or Hiddmentioning
confidence: 98%